Indirect search of heavy neutral leptons using the DUNE near detector - Carbajal, S.; Gago, A.M. (Frontiers Media, 2024)
We evaluate the potential of the DUNE near detector (DUNEND) for establishing bounds for heavy neutral leptons (HNLs). This is achieved by studying how the presence of HNLs affects the production rates of active neutrinos, therefore creating a deficit in the neutrino charged current (CC) events at the LArTPC of the DUNEND. The estimated bounds on HNLs are calculated for masses between 1 eV and 500 MeV. We consider 10 years of operation (five in neutrino and antineutrino modes) and obtain limits of | U μ 4 | 2 < 9 × 10 −3 (4 × 10 −2 ) and | U e 4 | 2 < 7 × 10 −3 (3 × 10 −2 ) for masses below 10 MeV and a 5% (20%) overall normalization uncertainty in the neutrino charged current event rate prediction. These limits, within the region of masses below 2 (10) MeV, are better than those that can be achieved by DUNE direct searches for the case of a 5% (20%) uncertainty. When a conservative 20% uncertainty is present, our limits can only improve current constraints on | U e 4 | 2 by up to a factor of 3 in a small region of approximately 5 eV and set limits on | U μ 4 | 2 in a mass region free of constraints (40 eV–1 MeV).
Keywords: Lepton; Detector; Physics; Particle physics; Environmental science; Nuclear physics; Remote sensing; Geology; Optics; Electron; https://purl.org/pe-repo/ocde/ford#1.03.03